Computer-based problem solving process - Rus, Teodor (World Scientific, 2015)
"The author looks at the issues of how computing are used and taught, with a focus on embedding computers within problem solving process by making computer language part of natural language of the domain instead of embedding problem domain in the computer by programming. The book builds on previous editions of system software and software systems, concepts and methodology and develops a framework for software creation that supports domain-oriented problem solving process adapting Polya's four steps methodology for mathematical problem solving: Formalize the problem; Develop an algorithm to solve the problem; Perform the algorithm on the data characterizing the problem; Validate the solution."-- Provided by publisher
Keywords: Computer-aided engineering.; Problem solving -- Data processing.; Mathematics -- Data processing.; elektronické knihy; electronic books